Nutritional Status of Children with Neurodevelopment Disorders from a Tertiary Medical Center of Bangladesh (BIRDEM Medical Journal, 2018)
Background: Cerebral palsy (CP), CP with epilepsy, epilepsy, speech delay, Down’s syndrome, autism, ADHD and vertigo are the most common disabilities among children in Bangladesh. Nutritional status assessment is important as these children are at risk of under nutrition, over nutrition or obesity. The primary objective of this study was to determine the nutritional status of children with neuro-disorder and secondary objective was to find out the factors correlated with poor nutritional status in these children.Methods: A retrospective study was conducted from a vast number of patients with neurodevelopment disorder attending the out-patient department (OPD) of Institute of Paediatric Neurodisorder and Autism (IPNA), BSMMMU, Dhaka with 149 sample cases from January 2015 to August 2015. Common indicators used to assess the nutrition status of neuro-disorder children were z-scores for weight-for-age, height-for-age, Body Mass Index-for-age percentile.Results: During the 8 months study period, a total of 149 children were taken aged from 1-180 months where Cerebral palsy (CP), CP with epilepsy, epilepsy, speech delay, Down’s syndrome, Autism, ADHD and Vertigo were included and most of the children’s nutritional status were CP had moderately impaired nutritional (53%),CP with epilepsy had mildly impaired nutritional status[(44%),Epilepsy and Speech delay both disorders had same moderately impaired nutritional status(53%),Autism had normal nutritional status(40%),children with Down’s syndrome had severely impaired nutritional status(43%), ADHD children were mostly obese(33%) & most of the children with vertigo had moderately impaired nutritional status (67%).Conclusions: In a developing country like Bangladesh it could be observed that children with Down’s syndrome were at risk of being severely impaired nutritional status, while children with CP, epilepsy, speech delay & vertigo were at risk of being moderately impaired nutritional status and children with ADHD were at risk of being overweight or obese. Children with autism had mostly normal nutritional status, while children of CP with epilepsy were at risk of being mildly impaired nutritional status. Beside low monthly income family with low aged child was somewhere related with nutrition status.Birdem Med J 2018; 8(2): 118-125